Recent Labor Market Performance in Vietnam through a Gender Lens - Pierre, Gaëlle (World Bank, Washington, DC, 2012)
This paper provides an overview of the recent performance of the labor market in Vietnam during the Great Recession. The analysis uses data from the Labor Force Survey and the Vietnam Household Living Standard Survey. The author finds that, notwithstanding the global crisis and domestic volatility, job creation has been sustained in Vietnam, especially in the formal sector, but that the overall quality of employment has suffered. Gender differentials are found to affect older women especially, while educated women benefit from a skills wage premium. Reassuringly given the large youth share of the total workforce, the youth labor market is dynamic and outcomes for youths have improved. Meanwhile, participation in poverty alleviation programs and labor market programs has not changed, and few workers use the newly created employment services and unemployment benefits.